Reverse spillover of avian viral vaccine strains from domesticated poultry to wild birds. Issue 28 (16th June 2017) - Rohaim, M.A.; El Naggar, R.F.; Helal, A.M.; Hussein, H.A.; Munir, Muhammad
Abstract: Transmission of viruses from the commercial poultry to wild birds is an emerging paradigm of livestock–wildlife interface. Here, we report the identification and isolation of vaccine strains of avian paramyxovirus serotype 1 (APMV1) and avian coronaviruses (ACoV) from different wild bird species across eight Egyptian governorates between January 2014 and December 2015. Surveillance of avian respiratory viruses in free-ranging wild birds (n = 297) identified three species that harboured or excreted APMV1 and ACoVs. Genetic characterization and phylogenetic analysis of recovered viruses revealed a close association with the most widely utilized vaccine strains in the country. These results highlight the potential spillover of vaccine-viruses probably due to extensive use of live-attenuated vaccines in the commercial poultry, and close interaction between domesticated and wild bird populations. Further exploring the full spectrum of vaccine-derived viral vaccine strains in wild birds might help to assess the emergence of future wild-birds origin viruses.